Ablation behavior of rare earth La-modified ZrC coating for SiC-coated carbon/carbon composites under an oxyacetylene torch. (March 2016) - Jia, Yujun; Li, Hejun; Feng, Lei; Sun, Jiajia; Li, Kezhi; Fu, Qiangang
Highlights: La-modified ZrC coating was prepared by supersonic atmosphere plasma spraying. The oxyacetylene ablation behavior of La-modified ZrC/SiC coating was evaluated. The coating shows a good ablation resistance under heat flux of 2.4 MW/m 2 . La promotes the liquid phase sintering of ZrO2 and the formation of a compact scale. The protection of the scale results in retaining elemental C in its inner layer. Abstract: To improve the ablation resistance of carbon/carbon (C/C) composites at ultra-high temperature, La-modified ZrC coating was prepared on SiC-coated C/C composites by supersonic atmosphere plasma spraying. The coating shows a significant improvement on the ablation resistance compared with ZrC coating and could protect C/C composites for more than 120 s under heat flux of 2.4 MW/m 2 . La acted as a role in promoting the liquid phase sintering of ZrO2 and forming a compact scale with high thermal stability, improving the ablation resistance of C/C composites.